Percepción empresarial de la mejora del enlace ferroviario Vigo-Oporto y modelización de la elección modal - Francisco Javier Sánchez Sellero; Maria Montserrat Cruz González (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
This work analyzes the use of the train by the Galician companies when they do business transactions with northern Portuguese operators. The residual usage of this infrastructure (0.01 of all the transactions) is proved opposite the masive use of the truck; factors that explain the choice and the possible truck-versus-train replacement are established. The statistical study includes representative industrial companies and the main consignees of regular lines in the port of Vigo as spectrum. A formative explained structural equation model and a linear regression of the modal choice and its effect on the referred replacement are suggested. As conclusion, the need of improvement of the infrastructures in the connection mentioned above is assessed by companies and logistic operators (these last ones are more interested in changing) although the real liberalization of the rail operators market is a priority as without this, the improvement mentioned above would not affect the modal choice significantly.
Keywords: C14; C51; F23; L92; R11; 330; managerial perception; railway connection Vigo - Oporto; railway operators market; modal election